Climate change and resilient practices for coastal agriculture - Rautaray, S. K.; Satapathy, B. S.; Sucharita, Swati; Sarangi, A. (Indian Farming, 2024)
Adverse effect of climate change is likely to be more in coastal areas with high density of population, ports, cities, trade centres, industries and plantation crops. Waterlogging during monsoon, while water scarcity, salinity build up and sea water intrusion during the dry season is likely to affect cropping season and yield. The cyclonic storms and depressions which affect India, originate and/ or intensify mostly over the Bay of Bengal. Incidents of lightning and thunderstorms have also increased in recent years. East Coast of India is vulnerable to flood, drought, moist heat, cyclones, and thunderstorms mandating integrated and multi-purpose resilient practices. Rainwater management is the key to tackle the excess and deficit water stress. Land modification for rice-fish- horticulture system, pond based farming system, and alternate raised bed and sunken bed with farming system are useful in coastal areas. Agroforestry using Casuarina, Eucalyptus, Acacia, palms and bamboo as part of land modification based farming system has multiple uses such as windbreak, bird shelter, biodiversity promotion, and bird guano collection for soil conditioning and fish feed. Palmyra palm trees help in arresting the enhanced menace of lightning and thunderstorms, and providing nutritious fruits and timber. Bamboo groves with high tenacity are useful in saving lives against high speed winds and high tides.